California and the Future of Partial Match DNA Investigations - Choi, Jenny (2012)
Though DNA testing has been successfuly used in the United States since the 1980s, many high profile prosecutions have thrust this forensic tool into general acceptance as well as the public consciousness. In 2008, California broke new forensic ground, authorizing partial match DNA testing to augment the arsenal of law enforcement tools. This proactive technique has yielded substantial results, but has also opened the door to criticism. This Note analyzes the history of DNA testing in California and nationally, including the progression towards partial match testing. This Note also considers constitutional, social, and policy concerns raised by the use of this forensic technique